Analysis of the Government's Role in Social Development Based on Development Administration at the Medan Mayor's Office - Maulana M Hamzah; Andri Soemitra (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2022)
Administration for development is the administration of and for development, which usually uses a management approach, because it is concerned with development management. In this case, development management includes development planning, resource mobilization and budgeting. All of these aspects ar e necessary because they see development needs that are greater than the availability of existing resources. Therefore, development planning is needed to make right judgements in accordance with the development vision. Development planning must be in line with optimal resource mobilization and appropriate budgeting.